OPTIMIZATION OF THE PROCESS FOR OBTAINING ANTIOXIDANT EXTRACTS RICH IN β-CAROTENE FROM THE RESIDUAL BIOMASS OF ARTHROSPIRA PLATENSIS - Alina Beşliu; Oleg Chiselița; Natalia Chiselița; Nadejda Efremova; Elena Tofan (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
This study aimed to optimize the process of obtaining antioxidant extracts rich in β-carotene from the remaining biomass of Arthrospira platensis. Optimal extraction procedures using ultrasound, homogenization and temperature were investigated at the laboratory level. The results demonstrated that the highest yield of β-carotene in the extracts was obtained using 96 % ethylic alcohol at a temperature of +45 °C for 30 minutes and a biomass/solvent ratio of 1 : 50 g·mL-1 and 1 : 10 g·mL-1 . The activity of the antioxidant enzymes catalase and superoxide dismutase varied depending on the extraction method, and the highest activity was obtained in the experimental variants that were placed at the temperature of +35 °C and +45 °C. Considering the valuable biochemical composition and enzymatic activity, the antioxidant extracts obtained have a relevant potential for implementation in various fields such as animal husbandry, medicine and food.